PENGELOLAAN DANA PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) - Mustajab, Muhammad; Izzati, Cut Rahmi (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
This research aims to find out the procedures for managing Rural Agribusiness Development (PUAP) funds, the obstacles in managing them and a review of Islamic law related to managing these funds. The research method used is a qualitative method. This type of research is field research using data collection techniques through observation, interviews and documentation review. The results of the research show that the Rural Agribusiness Development (PUAP) funds are managed by lending a certain amount of funds to farmer groups who are members of the PUAP group which are used for their farming needs to buy fertilizer, seeds and so on. The payment is more as a service of 10% of the loan principal as regulated in the PUAP provisions. In the management process, there were several obstacles faced by the administrators, including that there were some borrowers who did not pay on time, which made the cash condition of PUAP funds become congested and financial turnover became a little slow. And ultimately finances become limited and make farmers who have large areas of land unable to take out loans according to the size of their land. As well as crop failures which make farmers who take out loans unable to pay off their loans. Islamic law perspective, its management is still not in accordance with Islamic law.